IMPLEMENTASI ANTENA WAJANBOLIC SEBAGAI PENGUAT SINYAL UNTUK KONSEP PERTANIAN CERDAS DI PASAMAN SUMATERA BARAT - Bella Nofrianti; Ridwan Satrio Hadikusuma; Lela Nurpulaela (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
The use of Internet of Think(IoT) is widely used in the environment to increase production yields through intelligent agricultural decisions and obtaining crop information, measurement of temperature, humidity, and irrigation systems to the use of drones. However, the use of sensors in IoT has limited resources regarding restriction, energy, transmission, and memory capabilities which can negatively impact agricultural production. To transmit data from measurement results to sensors, fast internet network access is required. while on large farms it is not possible to install wifi in every corner of the farm. The purpose of this research is to strengthen the cellular signal through the application of wokbolic. Thus internet access in agricultural areas becomes easier and crop yields are increased by using the internet. The development of wokbolic uses a prototype model that is considered simple to be directly applied to rice fields. The results of the QoS test show that the throughput value at a distance of 50 m is 550 Kbps. The wokbolic captures the average signal times > 50 ms when using the internet. The application of a wireless router connected to a bolic wok can be accessed ± 50 meters from the wireless center. Keywords: IoT, agriculture, internet, transmission, wokbolic